Odpowiedź :
Odpowiedź:
a) 6x = 3 | : 6
6x : 6 = 3 : 6
x = 3/6
x = 1/2
b) -3x = 7 | : (-3)
-3x : (-3) = 7 : (-3)
x = -7/3
x = -2 1/3
c) 2x = 1/5 | : 2
2x : 2 = 1/5 : 2
x = 2/10 : 2
x = 1/10
d) 1,2x = 4,8 | : 1,2
1,2x : 1,2 = 4,8 : 1,2
x = 4,8/1,2
x = 48/12
x = 4
e) 1/3x = 3 | · 3
1/3x · 3 = 3 · 3
x = 9
f) -35/x = -5 | · x
-35/x · x = -5 · x
-35 = -5x | : (-5)
-35 : (-5) = -5x : (-5)
7 = x
x = 7
g) 3/4x = -4/9 | · 4
3/4x · 4 = -4/9 · 4
3x = -16/9 | : 3
3x : 3 = -16/9 : 3
x = -16/9 · 1/3
x = -16/27
h) 0,1x = -7 | · 10
0,1x · 10 = -7 · 10
x = 70
Odpowiedź:
a 6x=4-1
6x=3/6
x=1/2
b 3x=2,5-1
3x=1,5/3
x=1/2
c 3x-x=5-7
2x=-2/2
x=-1
D
3x=1,5/3
x=1/2
e x=1,8-2/3
x=9/5-2/3
x=17/15=1 cała 2/15